Exile [videorecording (DVD)] - Beaton, Michael; Beach, Adam, 1972-; Sullivan, Camille; Chalk, Garry, 1952- (Electric Entertainment, 2022)
Just prior to his release from prison, Ted Evans receives a threat from the man whose family he killed in a DUI 'if you make contact with your family, I'll kill them'. Believing that the danger is real, Ted exiles himself to a reclusive life to protect his family. However, Ted's wife knows the threat is merely a manifestation of her husband's profound guilt. Determined to rebuild their family, Sara tracks Ted down to confront him with hard evidence that the threat is imagined. But Sara has no idea just how unhinged Ted has become or how real the threat may be after all.